Analysis of the Effect of Products, Prices, Promotions and Referral Groups on Purchase Decisions for IM3 Ooredoo Products (Study on Millennial Generation at CV. Gagah Store Gresik) - Faerul Falaq (Universitas Muhammadiyah Gresik, 2021)
The IM3 cellular operator consecutively ranks second in the Top Brand for 2019-2021 byrecording a percentage increase every year from 12.70% to 14.60%, then to 16.30%. The millennialgeneration who entered the productive age amounted to 108,514,633 people in Indonesia in 2020 or57%. The purpose of this study was to determine the purchase decision of IM3 Ooredoo in CV. GagahStore in the millennial generation based on products, prices, promotions and referral groups.Sampling used proportionate stratified random sampling, with details of 29 people 20-24 years old, 29people 25-29 years old, 30-34 years old 14 people, 35-39 years old 9 people, 40-44 years old 6 people.The regression used in this study is multiple linear regression with the equation function obtained: Y =1.621 + 0.202X1 + 0.258X2 - 0.132X3 + 0.270X4 + e. In testing the hypothesis, namely the significancetest, product, price and reference group variables have an effect on purchasing decisions, whilepromotion variables have no effect on purchasing decisions.